Genetic variability and phenotypic diversity in populations of the Eurasian perch, Perca fluviatilis (Actinopterygii, Percidae) - Oxana N. Zhigileva; Anna G. Egorova (Acta Biologica Sibirica, 2022)
The Eurasian perch Perca fluviatilis (Linnaeus, 1758) is a common species of fish in northern ecosystems. The species demonstrates high phenotypic diversity when it inhabits various types of water bodies. Here, we investigate whether there is a relationship between the genetic variability and phenotypic diversity in natural perch populations. Perca fluviatilis samples (n = 218) were collected from seven localities in the Ob-Irtysh river basin in western Siberia, Russia. We used color morphs and standard morphometric approach to study phenotypic diversity, allozyme and ISSR-PCR markers to study the genetic variability of the perch. In total, 19 types of perch colouration were found. The number of color morphs varied from 4 to 16 in different reservoirs. The sets of colour morphs and prevailing coloration types, as well as some morphometric characteristics, were significantly different in all studied populations. Low allozyme variability was identified in the perch. The average observed and expected allozyme heterozygosity was 0.003 and 0.056, respectively; 13% of the loci were polymorphic. The genetic diversity (h) of the markers (ISSR) was 0.31; from 53% to 96% of the bands were polymorphic. Genetic differentiation in the perch was high, especially in allozyme loci. The FST and GST values were 0.39 and 0.085 for allozyme and ISSR markers, respectively. The genetic variability indices of the perch did not correlate with phenotypic diversity. Our results suggest that the use of different phenotypic or genetic markers can provide extremely different information on the level of variability in the population.